Production of Chimeric Acidic α-Amylase by the Recombinant Pichia pastoris and Its Applications - Parashar, Deepak; Satyanarayana, Tulasi (Frontiers in Microbiology, 2017)
Recombinant chimeric α-amylase (Ba-Gt-amy) has been produced extracellularly in P. pastoris under AOX promoter. Clones of P. pastoris with multiple gene copies have been generated by multiple transformations and Post-Transformational Vector Amplification (PTVA), which led to 10.7-fold enhancement in α-amylase titre as compared to a clone with a copy of the gene. The recombinant P. pastoris integrated 8 copies of Ba-Gt-amy in the genome of P. pastoris, as revealed by real time PCR data analysis. Heterologous protein expression as well as mRNA level of Ba-Gt-amy was higher in multi-copy clone than that with single copy. The pure Ba-Gt-amy expressed in P. pastoris is a glycoprotein of 75 kDa, which is optimally active at pH 4.0 and 60 °C with T1/2 of 40 min at 70 °C. The Kinetic parameters and end product analysis suggested that glycosylation has no effect on catalytic properties of Ba-Gt-amy. The enzyme saccharifies soluble as well as raw starches efficiently and generates maltose and maltooligosaccharides, thus, useful in baking and sugar syrup industries. The strategy for generating multi-copy clones is being reported for the first time, which could be useful in enhancing the production of other recombinant proteins.